2021
DOI: 10.1099/jgv.0.001658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immature tick-borne encephalitis virus particles on antiviral activity of 5-aminoisoxazole-3-carboxylic acid adamantylmethyl esters

Abstract: Tick-borne encephalitis virus (TBEV), a member of the genus Flavivirus, is common in Europe and Asia and causes a severe disease of the central nervous system. A promising approach in the development of therapy for TBEV infection is the search for small molecule antivirals targeting the flavivirus envelope protein E, particularly its β-n-octyl-d-glucoside binding pocket (β-OG pocket). However, experimental studies of candidate antivirals may be complicated by varying amounts and different forms of the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…Sample also contained a minute fraction of distorted particles, which were visually different from the normal particles. These distorted particles correspond to damaged, immature, and half-mature virions [ 25 , 26 ] ( Figure 1 ). By manually examining the dataset, we concluded that only 2% of the observed particles could be treated as distorted.…”
Section: Resultsmentioning
confidence: 99%
“…Sample also contained a minute fraction of distorted particles, which were visually different from the normal particles. These distorted particles correspond to damaged, immature, and half-mature virions [ 25 , 26 ] ( Figure 1 ). By manually examining the dataset, we concluded that only 2% of the observed particles could be treated as distorted.…”
Section: Resultsmentioning
confidence: 99%